1988
DOI: 10.1192/bjp.153.2.198
|View full text |Cite
|
Sign up to set email alerts
|

Carbamazepine vs Lithium in the Treatment and Prophylaxis of Mania

Abstract: Fifty-four acutely manic patients were allocated to treatment on a double-blind basis with either carbamazepine or lithium carbonate. The short-term effects of treatment were studied over a period of six weeks and the longer term, prophylactic, effects over a period of up to a year. Additional 'rescue' medication was allowed when clinically indicated. There was a high drop-out rate from the trial. Despite this, it appeared that valid comparisons between the two treatments could be made. No statistically signif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
73
0
3

Year Published

1991
1991
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 146 publications
(78 citation statements)
references
References 7 publications
2
73
0
3
Order By: Relevance
“…Several controlled studies corroborated carbamazepine's effectiveness in the acute treatment of mania and perhaps prophylaxis of the disorder (Okuma et al 1979(Okuma et al , 1990Coxhead et al 1992;Lusznat et al 1988;Small et al 1991;Watkins et al 1987). Most studies found it to be comparable to lithium in effectiveness, except for three studies (Okuma et al 1981;Lerer et al 1987;Watkins et al 1987).…”
Section: Carbamazepinementioning
confidence: 87%
“…Several controlled studies corroborated carbamazepine's effectiveness in the acute treatment of mania and perhaps prophylaxis of the disorder (Okuma et al 1979(Okuma et al , 1990Coxhead et al 1992;Lusznat et al 1988;Small et al 1991;Watkins et al 1987). Most studies found it to be comparable to lithium in effectiveness, except for three studies (Okuma et al 1981;Lerer et al 1987;Watkins et al 1987).…”
Section: Carbamazepinementioning
confidence: 87%
“…36,39,40,42,43,[47][48][49][50][52][53][54][55][56][57]60,61,[64][65][66][67]69,72,74,77 Two of these studies compared only different doses of lithium and are not considered in the analyses. 52,61 Trial details are summarised in Table 2 and presented in the data extraction tables (Appendix 6).…”
Section: Efficacy Of Pharmaceutical Interventions Lithiummentioning
confidence: 99%
“…47,53,57,60,72 All relapses Four trials provided data for all relapses and were included in both the base-case analysis and the best-case/worst-case sensitivity analysis. One trial 60 was excluded from the main analysis because participants were randomised while still in an acute phase of bipolar disorder.…”
Section: Lithium Compared With Carbamazepinementioning
confidence: 99%
See 2 more Smart Citations